Gender Differences in the Effect of Residential Segregation on Workplace Segregation among Newly Arrived Immigrants - Tiit Tammaru; Magnus Strömgren; Maarten van Ham; Alexander M. Danzer (Institute for the Study of Labor (IZA), 2015)
Contemporary cities are becoming more and more diverse in population as a result of immigration. Research also shows that within cities residential neighborhoods are becoming ethnically more diverse, but that residential segregation has remained persistently high. High levels of segregation are often seen as negative, preventing integration of immigrants in their host society and having a negative impact on people's lives. Segregation research often focuses on residential neighborhoods, but ignores the fact that a lot of interaction also takes place in other spheres of life, such as the workplace. This paper examines the role of residential segregation in workplace segregation among recently arrived immigrants. By using unique longitudinal register data from Sweden, we show that the role of residential segregation in workplace segregation differs in an important way for immigrant men and immigrant women.
Keywords: J15; J61; R23; 330; immigrants; residential segregation; workplace segregation; longitudinal analysis; Sweden